Education Management Information System (EMIS) and Its Implications to Educational Policy: A Mini-Review - Asio, John Mark R.; Leva, Erlinda F.; Lucero, Leilani C.; Cabrera, Wendell C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This paper intends to show the importance of the Education Management Information System (EMIS) as well as the trends, challenges, and implications to educational policy. To achieve this, the proponents did a mini-review. The paper searched the internet for relevant and timely research papers and articles mainly focusing on the education management information system. After garnering enough materials for the mini-review, the tedious task of evaluating and analyzing the concepts and contexts of each material took place. Based on the evaluation, this paper found that some studies have shown promising results and positive experiences with the implementation education management information system (EMIS) in their institution. However, some did not execute well due to several reasons and factors. In addition, some research papers provided essential recommendations and suggestions that will help solve these different problems of EMIS. In the end, the paper concluded and shared some significant implications that school administrators can use for future references for policy and decision-making.